Reaffirm the Communist Manifesto - Sison, Jose Ma. (Kasarinlan: Philippine Journal of Third World Studies; Vol 15 No 1 (2000): Economies in Flux, 2009)
More than 150 years into the foretold struggle between capital and labor, between the bourgeosie and the proletariat, the Communist Manifesto is here reaffirmed. While the communist goal of abolishing private ownership of the means of production remains unrealized due to the comprehensive orchestration of a state aided bourgeosie, the ruling class continues to prosper under the fragmented socialist threat. But as the Manifesto declared, the ruling class will not escape the worsening crisis of its own system. The proletariat can only take so much oppression and exploitation which now exists on a global scale. The next revolution wherein the communist would have relearned lessons of past triumphs and failures and taken into full account the evolving world capitalist order, may finally lead to the realization of the socialist dream and the final reaffirmation of the Manifesto.